Classroom Management: A Persistent Challenge for Pre-Service Foreign Language Teachers (2015)
This qualitative descriptive study aimed to ascertain the extent to which classroom management constituted a problem among pre-service foreign language teachers in a teacher education program at a public university in Colombia. The study also sought to identify classroom management challenges, the approaches to confronting them, and the alternatives for improving pre-service teachers’ classroom management skills. The results revealed that classroom management is a serious problem with challenges ranging from inadequate classroom conditions to explicit acts of misbehavior. Establishing rules and reinforcing consequences for misbehavior were the main approaches to classroom management, although more contact with actual classrooms and learning from experienced others were alternatives for improving classroom management skills.Este estudio cualitativo descriptivo buscó determinar en qué medida el manejo de clase constituye un problema para docentes practicantes de lenguas extranjeras en un programa de licenciatura en inglés en una universidad pública Colombiana. El estudio buscó identificar los desafíos de manejo de clase, el enfoque para afrontarlos, y las alternativas para mejorarlos. Los resultados revelaron que el manejo de clase es un problema serio que va desde condiciones inadecuadas del salón hasta actos explícitos de indisciplina. Establecer reglas y consecuencias por indisciplina fueron el principal enfoque de manejo de clase mientras que mayor contacto con sitios de práctica y aprender de otros con experiencia fueron alternativas de mejoramiento.